(untitled) (International Conference on Computers in Education, 2017)
Programmable robotics activities in science, technology, engineering and mathematics (STEM) education have been postulated to have positive impacts on Computational Thinking (CT) development. This study aims to discuss how these activities in primary school STEM education should be designed to nurture students with CT abilities. According to Sullivan and Heffernan (2016), CT learning progression with robotics consists of four stages, namely sequencing, causal inference, conditional reasoning, and systems thinking. Three examples about auto-piloting a robotic car to 1) run a square, 2) run along the white track, and 3) slow down and stop when it detects an obstacle are designed to illustrate the learning progression. The first example provides opportunities for students to develop their abilities of sequencing and causal inference. The second example demonstrates how conditional reasoning can be developed. The third example shows how systems thinking can be established. Based on this learning progression for CT development, an outline of STEM education with programmable robotics activities in formal and non-formal learning in primary schools is proposed. The key is that problem-solving should be the core of these STEM activities. Students’ knowledge in STEM related subjects in primary schools like science, mathematics and programming should be applied and in turn being consolidated.